Pengaruh Kepemimpinan Transformasional terhadap Motivasi Instrinsik dan Komitmen Kerja serta dampaknya terhadap Kinerja Pegawai - Dedi Hadian (Kontigensi : Jurnal Ilmiah Manajemen, 2018)
Numerous problem occurs due to many complaints from the public regarding the services in the "public services sector," especially services that deal directly with the community. This condition is allegedly due to poor employee performance. This study tries to determine the effect of transformational leadership on intrinsic motivation and work commitment and its impact on employee performance. This research carries out a survey of employees in an agency in West Bandung Regency to address the problems. Furthermore, this study uses the path analysis approach with SPSS. The results show that there is an influence of transformational leadership on intrinsic motivation and work commitment and its impact on employee performance.